Preparedness of general practitioners in providing health services to foreign tourists in Bali, Indonesia - Anak Agung Sagung Sawitri; Putu Cintya Denny Yuliyatni (Public Health and Preventive Medicine Archive, 2017)
Background and purpose: Bali was visited by more than 4.9 million foreign tourists in 2016. To some extent foreign tourists may need health services during their travel. This study aims to describe perception of preparedness of general practitioners (GPs) to provide health services for foreign tourists. Methods: Surveys were conducted among foreign tourists who visited Bali in 2012 and among GPs in 2013. Self-administered questionnaires on the level of satisfaction were completed by 108 foreign tourists. Structured questionnaires exploring the travel medicine knowledge and English language proficiency were completed by 109 GPs. The experience of foreign patients was used to triangulate the response from GPs. Result: Good satisfaction in terms of capacity of GPs to provide quality services reported by foreign tourists was varied between 76% and 85%. Assessment of level of knowledge among GPs regarding travel medicine showed that 33% GPs were having good knowledge, 55.1% fair and 11.9% poor. The proportion of correct answer of several items were low, which included recommended vaccine (11%), management of jetlag (13,8%), symptoms of barotrauma during diving (13,8%), sunburn and protection (31,2%), malaria prevention (21%), and diarrhea management (27,5%). Good satisfaction of English communication reported by foreign tourists was between 65% and 78%. Meanwhile, 60% GPs believed to have good English communication with their foreign patients. Conclusion: Preparedness of general practitioners to deliver health services and in English communication to foreign tourists was generally sufficient. Knowledge of GPs on several aspects of travel medicine was insufficient.